Ekologia w przypowieściach Jezusa - Andrzej Jacek Najda (Studia Ecologiae et Bioethicae)
Jesus during His public ministry concentrated Himself above all on teaching. He often made use of parables, in which He used a variety of motifs and presentations from the field of ecology, in order to be properly understood by His listeners. Making use of ecological images Jesus describes the beginning, development and reality of the Kingdom of God, He speaks about the time already begun of salvation and God’s reign, about God’s goodness and mercy, about the situation of His disciples in the world. He also calls for repentance and for the bearing of good fruit.